The Immunologic Properties of Undifferentiated Stem Cells from Human Exfoliated Deciduous Teeth (SHED) and Its Potential Application in Bone Regeneration - Abdullah, Dr. Nurul Asma (IIUM Medical Journal Malaysia, 2013)
Introduction: Stem cells from human exfoliated deciduous teeth (SHED) are highly proliferative, clonogenic cells capable of differentiating into osteoblasts and inducing bone formation. It is a potential alternative for stem cell bone regeneration therapy. However, stem cell therapy carries the risk of immune rejection mediated by inflammatory cytokines of the human defense system. Objective: This preliminary research studies the interaction between SHED and the immune system by determining the inflammatory cytokines profile and osteogenic potential of SHED. Methods: Human fetal osteoblasts (hFOb) cell line and isolated SHED were cultured and total RNA was extracted, followed by reverse transcription cDNA synthesis. Semi-quantitative reverse transcription PCR and Multiplex PCR were performed to detect the expression levels of OPG/RANKL and TNF-α, IL-1β, IL-6, IL-8 and TGF-β in both cell types. Results: Analysis showed that SHED expressed significantly lower amounts of IL-1β, IL-6, and IL-8 compared to hFOB. IL-1β is a potent bone-resorbing factor, while IL-6 and IL-8 induce osteoclastogenesis and osteolysis respectively. SHED did not express TNF-α which stimulates osteoclastic activity. SHED demonstrated high OPG/RANKL ratio, in contrast with that of marrow stem cells described in previous studies. Our findings suggest that SHED may have improved immunomodulatory profile in terms of promoting relatively lower inflammatory reaction during transplant and enhancing bone regeneration. Conclusion: SHED has a potential to be a good source of osteoblasts for bone regeneration therapy. Further studies on the immunomodulatory properties of SHED-derived osteoblasts are necessary to enable stem cell therapy in immunocompetent hosts